Improving Eco Enzyme Product Quality with Seven Tools and 5W+1H Methods - Nurhayati, Lilis; Widari, Nyoman Sri; Bellanov, Agrienta (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2025)
Eco-enzyme is a fermentation product of organic materials, which is beneficial to the environment, but often suffers from defects in its production. This research aims to improve the quality of eco-enzymes using the Seven Tools and 5W+1H methods. Seven Tools identifies the causes of defects, while 5W+1H formulates improvement strategies. The analysis results show that color defects or black mold is the main problem with a percentage of 46.15%. Causal factors include poor quality raw materials, low labor skills, and suboptimal processing methods. Improvements were made by selecting fresh organic ingredients, 20% leafless vegetable composition, 30-minute soaking, and more optimal stirring. This strategy is expected to improve product quality and reduce the level of defects in eco-enzyme production.